Efficacy of Thymol and Eugenol Against Polymicrobial Biofilm - Tunjung Pratiwi, Sylvia Utami; Hamzah, Hasyrul; Hertiani, Triana (Indonesian Journal of Pharmacy, 2018)
Biofilms associated with human infection have high levels of pathogenicity due to their resistance to antibiotics. The discovery of an active antibiofilm agent against polymicrobial biofilms is a necessary consequence for coping with biofilm-related infections. Thymol and Eugenol are essential oils that have potential as antibacterial and antifungal. This study aimed to determine the effectiveness of thymol and eugenol inhibits C. albicans, P. Aeruginosa, E. coli S. aureus and polymicrobial biofilm. Biofilm formation inhibition assay and biofilm degradation assay of thymol and eugenol were determined using microtiter broth method.The antibiofilm efficacy of thymol and eugenol towards polymicrobial biofilms were analyzed by calculating minimum biofilm inhibitor concentration (MBIC50) and minimum biofilm eradication concentration (MBEC50) values. The data were analyzed using Statistical Package for the Social Sciences (SPSS) with 95% confidence level. Thymol and eugenol showed inhibitory activity against the formation of mono and polymicrobial biofilms of the microbial tested.The result also demonstrated an evidence of activity of thymol and eugenol in breaking down mono and polymicrobial biofilm. Therefore, thymol and eugenol serves as a potential source for new antibiofilm drugs towards polymicrobial biofilm.